Improving Decision-Making Skills in Elementary Schools with Cognitive Flexibility Learning Media Incorporating Balinese Local Wisdom - I Ketut Satria Ardana; I Kadek Edi Yudiana (Thinking Skills and Creativity Journal, 2024)
This research is motivated by the low decision-making ability of elementary school students, the limited knowledge of Balinese local wisdom, the suboptimal learning models used, and the insufficient utilization of instructional media. The study aims to develop a prototype and determine the validity, practicality, and effectiveness of interactive learning media. This research adopts the Research and Development (R&D) approach using the ADDIE model. Data collection methods include interviews, observations, and questionnaires. The instruments used to collect data consist of observation guidelines, rating scale sheets, interview guidelines, and questionnaire forms. The research trial involved 19 fifth-grade elementary school students.The findings indicate that the interactive learning media based on Balinese local wisdom achieved a validity index of 0.943, classified as highly valid. The content validity index of the interactive learning media reached 0.937, also categorized as highly valid. The student response achievement level was 93.26%, while the teacher practitioner's response was 94.40%, both classified as excellent. Additionally, the correlated t-test significance value (2-tailed) was 0.000 or p < 0.05, confirming that the interactive learning media based on Balinese local wisdom is valid, practical, and effective in enhancing fifth-grade elementary students' decision-making skills.